Cardiorespiratory pathogenesis of sickle cell disease in a mouse model - Jun Ren (Nature Portfolio, 2017)
Abstract The nature and development of cardiorespiratory impairments associated with sickle cell disease are poorly understood. Given that the mechanisms of these impairments cannot be addressed adequately in clinical studies, we characterized cardiorespiratory pathophysiology from birth to maturity in the sickle cell disease SAD mouse model. We identified two critical phases of respiratory dysfunction in SAD mice; the first prior to weaning and the second in adulthood. At postnatal day 3, 43% of SAD mice showed marked apneas, anemia, and pulmonary vascular congestion typical of acute chest syndrome; none of these mice survived to maturity. The remaining SAD mice had mild lung histological changes in room air with an altered respiratory pattern, seizures, and a high rate of death in response to hypoxia. Approximately half the SAD mice that survived to adulthood had an identifiable respiratory phenotype including baseline tachypnea at 7–8 months of age, restrictive lung disease, pulmonary hypertension, cardiac enlargement, lower total lung capacity, and pulmonary vascular congestion. All adult SAD mice demonstrated impairments in exercise capacity and response to hypoxia, with a more severe phenotype in the tachypneic mice. The model revealed distinguishable subgroups of SAD mice with cardiorespiratory pathophysiology mimicking the complications of human sickle cell disease.